Introduction to the Science of Mantics; Definition, Laws, Goals and Benefits in Everyday Life - Didin Hidayat; Ratih Andriani Khasanah; Rama Prameswara Darma Putra; Siti Hopipah; Siti Mariam (Al-Falsafah: Jurnal Pemikiran dan Filsafat Islam, 2026)
Logic is a discipline that studies the relationship between symbols, numbers, and energy in human life and the universe. This research aims to provide a basic understanding of logic through an examination of its definition, main laws, objectives, and benefits in everyday life. The research method used is a literature study, collecting and analyzing literature sources related to logic from reference books, scientific articles, and relevant historical documents. The results show that logic has various definitions according to each tradition, inspired by basic laws such as the law of harmony, the law of cause and effect, and the law of energy. The primary goal of logic is to help humans understand themselves, optimize their potential, and maintain balance with their surroundings. Its practical benefits can be felt in various aspects of life, such as decision-making, social relationships, and future planning. This research is expected to provide clear guidance for those who wish to study logic and apply it wisely.